Management of dyslipidaemia in individuals with severe mental illness: a population-based study in the Greater Copenhagen Area - Grimur Høgnason Mohr; Carlo Alberto Barcella; Mia Klinten Grand; Margit Kriegbaum; Volkert Siersma; Margaret K. Hahn; Sri Mahavir Agarwal; Catrine Bakkedal; Lone Baandrup; Filip Krag Knop; Christen Lykkegaard Andersen; Bjørn Hylsebeck Ebdrup (SAGE Publishing, 2023)
Background: Severe mental illness (SMI) is associated with increased cardiovascular risk. Dyslipidaemia is a potentially modifiable risk factor, which may be inadequately managed in patients with SMI. Objectives: To assess management of dyslipidaemia in patients with SMI versus healthy controls (HCs) in 2005 and 2015. Design and methods: Using Danish registers, we identified adult patients with SMI in the Greater Copenhagen Area (schizophrenia spectrum disorders or bipolar disorder) with ⩾1 general practitioner contact in the year before 2005 and 2015, respectively, and HCs without SMI matched on age and gender (1:5). Outcomes were lipid-profile measurements, presence of dyslipidaemia and redemption of lipid-lowering pharmacotherapy. Differences in outcomes between patients with SMI and controls were measured with multivariable logistic regression. Results: We identified 7217 patients with SMI in 2005 and 9939 in 2015. After 10 years, patients went from having lower odds of lipid measurements to having higher odds of lipid measurements compared with HCs [odds ratio (OR) 2005 0.70 (99% confidence interval (CI) 0.63-0.78) versus OR 2015 1.34 (99% CI 1.24-1.44); p 2005 versus 2015  < 0.01]. Patients had higher odds of dyslipidaemia during both years [OR 2005 1.43 (99% CI 1.10-1.85) and OR 2015 1.23 (99% CI 1.08-1.41)]. Patients went from having lower odds of receiving lipid-lowering pharmacotherapy to having higher odds of receiving lipid-lowering pharmacotherapy [OR 2005 0.77 (99% CI 0.66-0.89) versus OR 2015 1.37 (99% CI 1.24-1.51); p 2005 versus 2015  < 0.01]. However, among persons at high cardiovascular risk, patients had lower odds of receiving lipid-lowering pharmacotherapy during both years, including subsets with previous acute coronary syndrome [OR 2005 0.30 (99% CI 0.15-0.59) and OR 2015 0.44 (99% CI 0.24-0.83)] and ischaemic stroke or transient ischaemic attack (TIA) [OR 2005 0.43 (99% CI 0.26-0.69) and OR 2015 0.61 (99% CI 0.41-0.89)]. Conclusion: These results imply an increased general awareness of managing dyslipidaemia among patients with SMI in the primary prophylaxis of cardiovascular disease. However, secondary prevention with lipid-lowering drugs in patients with SMI at high cardiovascular risk may be lacking.